3D printing mesoporous bioactive glass/sodium alginate/gelatin sustained release scaffolds for bone repair. (January 2019) - Wu, Jingwen; Miao, Guohou; Zheng, Zhichao; Li, Zhengmao; Ren, Wen; Wu, Caijuan; Li, Yuanjing; Huang, Zhu; Yang, Lan; Guo, Lvhua
Drug delivery and release are a major challenge fabricating bone tissue engineering. In this study, we fabricated new sustained release hydrogel scaffolds composited of mesoporous bioactive glass, sodium alginate and gelatin by a three-dimensional printing technique. Naringin and calcitonin gene-related peptide were used as drugs to prepare drug-loaded scaffolds by direct printing or surface absorption. The physicochemical properties of the scaffolds and the drug release profiles of the two drug-loading models were investigated. We also examined the biocompatibility of the scaffolds, as well as the effect of the released medium on the proliferation and osteogenic differentiation of human osteoblast-like MG-63 cell. The results showed that the scaffolds had a high porosity (approximately 80%) with an interconnected cubic pore structure, rough surface morphology, bioactivity and strong biocompatibility. Furthermore, the naringin or calcitonin gene-related peptide co-printed into the scaffold displayed a steady sustained release behaviour for up to 21 days without an initial burst release, while both naringin and calcitonin gene-related peptide absorbed onto the surface of the scaffold were completely released within two days. MG-63 cells cultured with the extraction containing released drugs displayed promoted cell proliferation and the expression of osteogenesis-related genes more effectively compared with the drug-free extractions. Therefore, these results demonstrate that the developed mesoporous bioactive glass/sodium alginate/gelatin sustained release scaffolds provide a potential application for bone tissue engineering.